Criminalistic methodics of crime investigation: Current problems and promising research areas - SHEVCHUK, Viktor; VAPNIARCHUK, Viacheslav; BORYSENKO, Igor; ZATENATSKY, Dmytro; SEMENOGOV, Viacheslav (Revista Jurídica Portucalense, 2022)
The relevance of this study is to examine the sphere of criminalistic methodics of crime investigation, as the last section of criminalistic science, and to consider the problems of this sphere and the prospects for its improvement and reform. The purpose of this research is to examine the scope of criminalistic methodics of crime investigation and to study the main problems and prospects for improving the methodics of investigation of committed acts in accordance with the current criminal activity in Ukraine. The methods used to study this subject include dialectical, legal recognition, formal legal, hermeneutical, logical-legal, structural-functional, etc. The results of this study are the characteristics of the following section of criminalistic science –criminalistic methodics of crime investigation, the main problems of this area, the means and methods of improving the methods of investigation of committed acts for effective detection of crimes and impartial consideration of a criminal case. In the course of the research, the "criminalistic methodics of crime investigation" was defined; a distinction was made between the "criminalistic methodics" and "criminalistic methodics of crime investigation"; the essence, tasks, and functions of the criminalistic methodics of crime investigation were determined; problems and prospects for improving criminalistic methodics of investigation of crimes committed were identified. The provisions that are enshrined in this study are of practical value primarily for participants in criminal proceedings for the full and comprehensive protection of their procedural rights and impartial and objective consideration of their case, for law enforcement agencies, investigators, defence counsels, judges, and prosecutors whose activities are related to the investigation and consideration of a criminal case.